(untitled) (Swiss Medical Weekly, 2019)
Our senses are the main information channels through which we perceive and interact with the world. Consequently, the physical and social functioning of patients suffering from severe sensory disabilities is limited on several levels. This has motivated the development of a novel therapeutic alternative: “artificial senses”, more commonly known as sensory neuroprostheses. In order to restore lost function, sensory neuroprostheses attempt to take advantage of the information transfer pathway common to all senses: (i) transduction of the physical stimulus by sensory receptors, (ii) transmission of relevant information to primary sensory areas in the brain by sensory afferents, and (iii) analysis and integration of the information at multiple levels in the central nervous system. Neurosensory deficits might occur upon damage to any of the structures involved in this process. However, damage to the peripheral sensory receptor is often the cause of neurosensory loss. Most sensory neuroprostheses attempt to “replace” the malfunctioning or missing peripheral sensory organ by directly delivering basic sensory information to the brain using electrical currents. If the prosthesis is able to deliver enough consistent information, the brain will be able to correctly interpret it and useful rehabilitation can be achieved. This review presents the main challenges related to the development, implementation and translation to clinical practice of these devices: (i) sensory information needs to be efficiently delivered to specific neural targets (e.g., peripheral afferents or specific central nuclei); (ii) then the expected physiological response must be evoked and quantified; (iii) the restoration of basic sensory abilities can lead to useful rehabilitation in meaningful everyday activities; (iv) optimal prospects require specific rehabilitation therapy and lifelong medico-technical follow-up. To conclude, the current state and future of sensory neuroprostheses will be discussed. This will include current clinical and technical challenges, future prospects, and the potential of these devices to improve our fundamental knowledge of sensory physiology and neurosensory deficits.